Efektivitas penggunaan anggaran belanja terhadap biaya operasional sebagai alat ukur penilaian kinerja pemerintah pada Badan Pendapatan Daerah Kota Manado - Uisuma, Putri Melani L; Lambey, Robert (Yayasan Widyantara Nawasena Raharja, 2024)
The Manado City Regional Revenue Agency as a regional apparatus (SKPD) is based on Manado City Regional Regulation No. 1 of 2019 concerning the establishment and composition of Manado City regional apparatus and Manado Mayor Regulation No. 11 of 2019 concerning the position, organizational structure, objectives and functions and work procedures of the Manado City Regional Revenue Agency.In the work program implemented, there are assumptions that may become problems with budget realization in the future. This study aims to determine the expenditure budget in assessing performance through the Effectiveness Calculation at the Manado City Regional Revenue Agency. The type of research used is a qualitative method, the data processed is in the form of Budget Realization Reports and Physical and Financial Realization of the Manado City Regional Revenue Agency from 2020 to 2022. The technique used is measuring effectiveness in the 2020 to 2022 budget report. The results of this study state that in the results of the effectiveness ratio, it is stated that in 2020 and 2022 the criteria are